Comparison of Essential Oil Yield, Chemical Composition and Biological Activities of Eucalyptus camaldulensis Leaf: Conventional Distillation versus Emerging Superheated Steam Distillation - Saleh, Muhammad Tahir; Ayub, Muhammad Adnan; Shahid, Muhammad; Raza, Muhammad Haseeb; Hussain, Amjad; Javed, Tariq (Iranian Journal of Pharmaceutical Sciences, 2023)
Eucalyptus essential oil (EO) has significance economically since it is used in the medicinal and fragrance industries. The main objective of this study was to investigate the differences in yield, composition, antioxidant capacity, and antibacterial effectiveness of the EO extracted from Eucalyptus camaldulensis leaves. To achieve this, three distinct extraction techniques, namely steam distillation (SD), hydro distillation (HD), and superheated steam distillation (SHSD), were utilized to isolate the EO. The study aimed to analyze and compare these parameters among the three extraction methods. Based on the findings from the experiments, it has been found that using SHSD resulted in a higher EO yield than conventional techniques, and this SHSD produced a greater amount of EO in a shorter time. The EOs extracted using all three techniques have 1,8 cineole as the main constituent, according to gas chromatography-mass spectrometry (GC-MS) analysis results. All of the EOs demonstrated significant antioxidant capacities when tested in vitro using a variety of antioxidant assays. The EOs extracted through HD showed greater antibacterial activity among the other extraction processes, as evaluated by agar well diffusion and resazurin microtitre-plate assays. In conclusion, SHSD is more efficient for extracting EOs and antioxidant activity than traditional HD and SD.